(untitled) (Journal of Geography and Environmental Management, 2019)
Recently, the demand for tobacco products and, accordingly, its production in the world has been steadily falling. At the same time, of course, tobacco companies have to look for new ways to solve problems with lower incomes, where the tourism industry can play an unimportant role in solving this problem. The relevance of this topic is based on the study and disclosure of the main purpose of creating thematic routes, which affect the integration of non-viable attractions in the supply chain of products. The scientific idea of the study is to consider foreign sources, materials, world experience with regard to the study of this issue, to analyze and determine the possibility of developing thematic routes based on tobacco growing in Kazakhstan. The study is based on research using a combination of abstract-logical and economic-statistical methods of scientific cognition. Conducted research can contribute to the use of previously unused resources for tourism, along with obtaining a new clientele, requiring an appropriate type of tourism. The practical significance of the work results may be of interest to non-governmental organizations; supported by the government, tobacco companies, tour operators or other sponsors.